HIV-1 and opiates modulate miRNA profiles in extracellular vesicles - Caobi, Allen; Bonilla, Jesenia; Gomez, Mario; Andre, Mickensone; Yndart, Adriana; Fernandez-Lima, Francisco A.; Nair, Madhavan P.; Raymond, Andrea D. (Frontiers in Immunology, 2023)
Opiate abuse increases the risk of HIV transmission and exacerbates HIV neuropathology by increasing inflammation and modulating immune cell function. Exosome-bound miRNAs may be differentially expressed due to HIV infection or opiate abuse. Here we develop a preliminary exosomal-miRNA biomarker profile of HIV-infected PBMCs in the context of opiate use. PBMCs were infected with HIV and exposed to increasing dosages of morphine, exosomal miRNA was isolated and then analyzed via Nanostring and Webgestalt alongside assaying neuronal cell function. HIV-1 infection altered the miRNA profile of PBMC-derived EVs concurrently with opiate exposure. Such as hsa-miR-1246 displaying a 12-fold up-regulation in the presence of morphine, relative to uninfected control. PBMCs infected with HIV-1 MN (HIV-MN), an X4-tropic HIV-1 strain, in addition to exposure to morphine, displayed a trend which suggests potential synergistic effects between HIV-1 infection and morphine exposure promoting an increase in HIV-MN replication. Dose-dependent differences were also observed in miRNA expression as a result of opiate exposure. xEVs derived from PBMCs exposed to a multitude of treatments modulated neuronal cell function, with SH-SY5Y cells, treated with xEVs derived from ART-treated PBMCs, presenting with increased the cellular viability and SH-SY5Ys exposed to xEVs derived from HIV-1 infected PBMCs presenting with decreased viability when compared to the treatment. Exposing SH-SY5Y cells to xEVs derived from HIV-infected PBMCs resulted in a significant decrease of calcium signaling, relative to treatment with xEVs derived from uninfected PBMCs. Overall, HIV-1 and morphine induced differential miRNA expression in PBMCderived exosomes, potentially identifying mechanisms of actions or novel therapeutic targets involved in opiate use disorder, HIV neuropathology, the neuronal system, TNF signaling pathway, NF-kB signaling pathway, autophagy, and apoptosis. Understanding how morphine and HIV infection cargo could ultimately lead to identifying miR cargoes that alter cellular biology in context of HIV infection and opiate use; potentially identifying novel therapeutic targets of opiate use in context of HIV infection.